Communicating With Breast Imaging Patients During the COVID-19 Pandemic: Impact on Patient Care and Physician Wellness. Issue 2 (17th March 2022) - Milch, Hannah S; Grimm, Lars J; Plimpton, Steven R; Tran, Khai; Markovic, Daniela; Dontchos, Brian N; Destounis, Stamatia; Dialani, Vandana; Dogan, Basak E; Sonnenblick, Emily B; Zuley, Margarita L; Dodelzon, Katerina
Abstract: Objective: Assess the impact of COVID-19 on patient-breast radiologist interactions and evaluate the relationship between safety measure–constrained communication and physician wellbeing. Methods: A 41-question survey on the perceived effect of COVID-19 on patient care was distributed from June 2020 to September 2020 to members of the Society of Breast Imaging and the National Consortium of Breast Centers. Non-radiologists and international members were excluded. Anxiety and psychological distress scores were calculated. A multivariable logistic model was used to identify demographic and mental health factors associated with responses. Results: Five hundred twenty-five surveys met inclusion criteria (23% response rate). Diminished ability to fulfill patients' emotional needs was reported by 46% (221/479), a response associated with younger age (OR, 0.8 per decade; P < 0.01), higher anxiety (OR, 2.3; P < 0.01), and higher psychological distress (OR, 2.2; P = 0.04). Personal protective equipment made patient communication more difficult for 88% (422/478), a response associated with younger age (OR, 0.8 per decade; P = 0.008), female gender (OR, 1.9; P < 0.01), and greater anxiety (OR, 2.6; P = 0.001). The inability to provide the same level of care as prior to COVID-19 was reported by 37% (177/481) and was associated with greater anxiety (OR, 3.4; P < 0.001) and psychological distress (OR, 1.7; P = 0.03). Conclusion: The majority of breast radiologists reported that COVID-19 has had a negative impact on patient care. This perception was more likely among younger radiologists and those with higher levels of anxiety and psychological distress.